Perkuatan Lereng Jalan Menggunakan Shotcrete Pembangunan Ruas Jalan Segmen 01 Tawang-Ngalang (Studi Kasus Proyek Jalan PT. Arena Reka Buana) - Yudi Dwi Kurniawan, Yudi Dwi Kurniawan; Novandri Kusuma Wardana,; Anggi Hermawan, (ReTII, 2022)
One of Indonesia's geographical problems is that there are many differences in the elevation of the ground surface that have the potential to cause natural disasters, especially landslides. One example is in the plan for the construction of the 01 Tawang-Ngalang segment of the road which is constrained by deep excavation so that there are elevation differences that form a slope. The purpose of this study was to find the factor of safety (FK) of the slopes in the original condition and the condition after reinforcement with soil nailing and shotcrete and to find the effect of soil nailing geometry on the value of the safety factor using the limit equilibrium method and using Slide V7.0 software by rocscience. Material properties are obtained from the results of physical properties tests and mechanical properties tests in the laboratory. Meanwhile the slope geometry and specifications for shotcerete and soil nailing are not changed. Based on the results of the analysis, the FK values ​​of the unreinforced slopes ranged from 0.736 to 0.987 using the Bishop, Janbu, Morgenster and Price method. After strengthening with variations in length 0.5H, 0.75H and 1H with angles of 20°, 25°, 30° and 35°, the lowest FK value was 1.033 and the highest FK was 1.772. The effect of angle on soil nailing only increases FK 0.5%-3% and the effect of soil nailing length on FK value is 8%-15%. At Sta 1+800 the effective geometry is 0.75H with angle 27.5°, Sta 1+825 0.75H with angle 29° and Sta 1+850 1H with angle 31°.